The Problem of Fregean Equivalents. (14th November 2019) - Kim, Joongol
Abstract: It would seem that some statements like 'There are exactly four moons of Jupiter' and 'The number of moons of Jupiter is four' have the same truth‐conditions and yet differ in ontological commitment. One strategy to resolve this paradoxical phenomenon is to insist that the statements have not only the same truth‐conditions but also the same ontological commitments; the other strategy is to reject the presumption that they have the same truth‐conditions. This paper critically examines some popular versions of these two strategies, and defends a new solution according to which the statements have the same ontological commitments and yet differ in truth‐conditions.